A The Formulation of Non-Fired Bricks With Na-Based as Stabilisers and Sand as Additive - OMAR, NUR AISYAH NABILAH; C, CHEE MING; A R, Noor Khazanah (Progress in Engineering Application and Technology, 2023)
The formulation of non-fired bricks with Na-based acts as stabilizers with granular additives (sand) was the main issue that was being studied. Non-fired bricks can replace the use of fired bricks, especially in countries that were having a hard time making fired bricks because fired bricks need a high-temperature oven. Fired at high temperature cause the fired bricks to emit the greenhouse gasses and other pollutants due to the CO2. Furthermore, the combination of laterite, sodium silicate, sodium hydroxide, water, and sand were the substance that being used for making non-fired bricks in this studied. Both of the substance which is sodium hydroxide and sodium silicate were alkali activators. It was the alkaline solution that acts as an activator in the geopolymerization process to give an effect on the bricks. The geopolymer can increase the strength, durability and workability of non-fired bricks. The effect of mix proportions of various ratio (0.9, 1.1, 1.3, 1.5, 1.8) on mechanical properties of bricks were investigate. The result showed that the last mix proportion was the best ratio between laterite soil bricks and laterite soil-sand bricks. The compressive strength for both bricks were 11.5% and 12.3% respectively. This is due to the presence of sodium silicate in the solution which had more than sodium hydroxide, thus it lead to silica gel that can increase the compressive strength of bricks. The laterite soil- sand bricks was higher than laterite soil brick was prior to the addition of sand in the bricks. In addition, non-fired bricks have an advantage compare with fired brick in construction industry in term of climate change and sustainable consumption and productivity.